STUDI HERMENEUTIKA PENGENDALIAN INTERN PEMBERIAN KREDIT BADAN USAHA MILIK DESA (BUMDes) - Jumaiyah Jumaiyah; Aulia Fanandia Mawardiani (Jurnal Aplikasi Bisnis, 2018)
Internal control is the spirit of BUMDes success. Therefore, the security of lending should be considered. The purpose of this study was to find out how the internal control in BUMDes Giri Samudra in Jambu Village Mlonggo Sub-district of Jepara Regency. The research method used qualitative with deep hermeneutical approach to understand the forms of communication symbols by the BUMDes at the time of granting credit. The results of research that has been done indicate the existence of internal control in crediting system at BUMDes Giri Samudra Desa Jambu not apply Internal regulation with maximum